Evaluasi Tingkat Efisiensi Penggunaan Energi Kajian Ex Post Facto Penerapan Standar Green Building Gedung A ITSB - Muhammad Arief Irfan (PLANNERS INSIGHT : URBAN AND REGIONAL PLANNING JOURNAL, 2019)
In Indonesia, until 2016, there were only 11 building units that were successfully certified by green building by the Green Building Council Indonesia (GBCI). The eleven buildings are classified as new building and claimed to be 43% efficient. The issue of energy efficiency in buildings is increasingly becoming a real action. As the first campus in Indonesia to be certified green building with the title of gold, Building A Bandung Institute of Technology and Science (ITSB), located in Cikarang, is expected to be an environmentally friendly pilot building and also a building capable of achieving energy efficiency targets. The building, which began construction in 2009 and completed in 2011, is one of the new building categories that is very well used as an evaluation object. Since its operation in 2012, the ITSB building has never been the object of study regarding the level of efficiency in energy use. The research carried out using the energy audit method for the ITSB building shows that there are levels of energy efficiency, especially electricity use, in the period of 2013 to 2017. From this period data, studies of building performance can be carried out with energy efficiency opportunities in the future. future.